PENANAMAN PENDIDIKAN ISLAM TERHADAP ANAK DALAM KANDUNGAN - Imas Jihan Syah (Universitas Islam Lamongan, 2017)
Education is an aspect in human development that needs to take into account. This is because education is an effort to foster and develop the potential of human beings both spiritually and physically. Through education it is expected that individuals can grow and develop in accordance with the potential that God has given to them so that they can become mature human and be useful for the surrounding communities. Given the importance of education, the writer tries to explain that education, especially religious education (Islamic education) is a process that is done in stages in accordance with the phases of human development.